Recovery of the first and second phases of the M wave after prolonged maximal voluntary contractions. (February 2020) - Rodriguez-Falces, Javier; Malanda, Armando; Lavilla-Oiz, Ana; Navallas, Javier
Abstract: Introduction: We compared the recovery of muscle electrical properties after maximal voluntary contractions (MVCs) of 1 and 3 min duration by examining separately the first and second phases of the muscle compound action potential (M wave). Methods: M waves were evoked by supramaximal single shocks to the femoral nerve throughout the 30-min recovery following 1-min and 3-min MVCs. The amplitude, duration, and area of the M-wave first and second phases, along with peak-to-peak amplitude and total area, were measured from the knee extensors. Results: (1) The amplitude of the M-wave first phase increased to the same extent (and had the same time course of recovery) after the 1 and 3-min MVCs, whereas the amplitude of the second phase increased more markedly after the 1-min than after the 3-min MVC (P < 0.05). (2) The first phase remained enlarged for 2 min after exercise, whereas the augmentation of the second phase only lasted for 30 s. (3) After 30 min of recovery, the amplitude, area, and duration of both the first and second phases were decreased compared to control values (P < 0.05). Conclusions: The similar enlargement of the M-wave first phase after the 1 and 3-min MVCs suggests that the extracellular K + concentration attained after these contractions was similar. The mechanisms responsible for the long-term decreases in M-wave amplitude and duration are unknown at present, but are likely due to a decrease in the amplitude of individual transmembrane potentials and an increase in conduction velocity.